2010
DOI: 10.1186/1423-0127-17-81
|View full text |Cite
|
Sign up to set email alerts
|

Association of phospholipase A2 receptor 1 polymorphisms with idiopathic membranous nephropathy in Chinese patients in Taiwan

Abstract: BackgroundIdiopathic membranous nephropathy (IMN) is one of the most common forms of autoimmune nephritic syndrome in adults. The purpose of this study is to evaluate whether polymorphisms of PLA2R1 affect the development of IMN.MethodsTaiwanese-Chinese individuals (129 patients with IMN and 106 healthy controls) were enrolled in this study. The selected single nucleotide polymorphisms (SNPs) in PLA2R1 were genotyped by real-time polymerase chain reaction using TaqMan fluorescent probes, and were further confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 26 publications
6
57
0
7
Order By: Relevance
“…Coenen et al (29) found no evidence to support this hypothesis; in a cohort of 95 IMN patients, only 9 patients carried rare sequence variants in the PLA2R1 gene, and only 4 of the 9 patients were among the 60 patients who presented circulating autoantibodies against PLA2R. Our study provides additional support to the previously found associations between IMN and common coding and noncoding variants within PLA2R1 and HLA-DQA1 genes (14,18,19,29). Interestingly, the disease-associated genotype of PLA2R1 (rs4664308) is the common genotype, which was previously reported (14,30).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Coenen et al (29) found no evidence to support this hypothesis; in a cohort of 95 IMN patients, only 9 patients carried rare sequence variants in the PLA2R1 gene, and only 4 of the 9 patients were among the 60 patients who presented circulating autoantibodies against PLA2R. Our study provides additional support to the previously found associations between IMN and common coding and noncoding variants within PLA2R1 and HLA-DQA1 genes (14,18,19,29). Interestingly, the disease-associated genotype of PLA2R1 (rs4664308) is the common genotype, which was previously reported (14,30).…”
Section: Discussionsupporting
confidence: 71%
“…Many genes within the HLA locus have previously been associated with IMN (15)(16)(17). Moreover, other SNPs within PLA2R1 have been associated with IMN in Taiwanese and Korean populations (18,19). Additional studies to identify and validate genetic risk factors for IMN in independent populations may help to elucidate its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in this gene have also been shown to be associated to iMN susceptibility in two candidate gene association studies performed in Korea and Taiwan. 6,7 These findings together suggest an important role for PLA2R1 in the pathogenicity of iMN.…”
mentioning
confidence: 78%
“…10,11 The other two nonsynonymous SNPs identified in this study (rs35771982; p.His300Asp and rs3828323; p.Gly1106Ser) have Table 2. Sequence variants in PLA2R1 observed in 60 anti-PLA2R1-positive patients previously been shown, in candidate gene association studies that tested only single SNPs, to be associated with iMN by groups from Taiwan (p.His300Asp) 6 and Korea (p.His300Asp, p.Gly1106Ser). 7 Both SNPs reached significance for allelic association with iMN in the present study (P=1.6310 23 for rs3828323 and P=5.7310 26 for rs35771982) and might be particularly relevant also because they were identified in ethnically distant populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation